Electric Idyll. - Schewe, P.F.
Idaho Power Co. has so far resisted pressure from the Federal Energy Regulatory Commission to sell its transmission lines to independent companies. With the support of the Idaho Public Utilities Commission, Idaho Power feels that unbundling transmission from generation may foster competition but will not help improve price and reliability. Considered as one of the better managed utilities in the US, Idaho Power has had to deal with an average of 10,000 new customers moving into its service area every year. This means the utility has had to increase generation by about two percent a year, without incurring excessive environmental costs. Company officials have also expressed concern over the abating river flow, which could affect the utility's hydropower resource, and the anticipated imposition of a carbon tax by Congress in an effort to reduce greenhouse gas emissions
Keywords: Federal Energy Regulatory Commission; Idaho Power Co; Idaho Public Utilities Commission; Carbon tax; Energy market; Greenhouse gas emissions reduction; Hydropower resource; Independent companies; Transmission lines